Development and Evaluation of Self-propelled Multicrop Planter for Hill Agriculture - Singh, Hijam Jiten; De, Dipankar; Sahoo, P. K.; Iquebal, M. A. (Journal of Agricultural Engineering, 2014)
A two-row self-propelled multicrop planter for hilly areas was developed, and its performance evaluated for planting of maize and soybean seeds. Power was transmitted from a 1.57 kW engine to the drive wheels and metering mechanism through chain and sprockets. Inclined plate type seed metering mechanism was used in the planter. Seeds were placed in the furrows at desired depths through adjustable system. The average depths of seed placement were 22.50 mm and 21.50 mm for maize and soybean, respectively. The average draft requirement for the planter was 1.57 kN, which was within the capacity of the power source. Average field capacity of 0.11 ha.h-1 was obtained for continuous operation of the planter at an average forward speed of 1.36 km.h-1 for planting bothmaize and soybean. The average field efficiency and field machine index of the planter were observed to be 80.98and 71.78 %, respectively. The man-hour requirement for planting of one hectare land with the planter was 9.09. The cost of sowing with the planter was Rs.1100/- per hectare, which saved 64.80 % operational costs as compared to manual planting. The savings in man-hours and cost of planting were substantial.